A broadband capacitive sensing method for label-free bacterial LPS detection - Rydosz, Artur; Brzozowska, Ewa; Górska, Sabina; Wincza, Krzysztof; Gamian, Andrzej; Gruszczynski, Slawomir (Biosensors & bioelectronics, 2016)
In this paper, the authors present a new type of highly sensitive label-free microwave sensor in a form of interdigital capacitor coated with T4 bacteriophage gp37 adhesin. The adhesin binds Escherichia coli B (E. coli B) by precise recognizing its bacterial host lipopolysaccharide (LPS). The C-terminal part of the adhesin consists of the receptor-binding amino acid residues which are involved in a specific interaction with two terminal glucose residues of the bacterial LPS. The change of the sensors' capacitance and conductance as a subject to LPS presence is an indicator of the detection. The measurements in the frequency range of 0–3GHz utilizing vector network analyzer have been carried out at different concentrations to verify experimentally the proposed method. The measured capacitance change between the reference and the biofunctionalized sensor equals 15% in the entire frequency range and the measured conductance change exceeds 19%. The changes of both parameters can be used as good indicators of the LPS detection. The selectivity has been confirmed by the ELISA experiments and tested by sensor measurements with lipopolysaccharide (LPS) from E. coli B, E. coli 056, E. coli 0111, Pseudomonas aeruginosa NBRC 13743 and Hafnia alvei 1185. •A novel broadband method for microwave detection of LPS is proposed.•The specificity of the method is ensured by the use of T4 bacteriophage gp37 adhesin.•The change of sensor parameters is significantly distinguish in LPS presence.